Penguatan Pendidikan Kesetaraan Gender untuk Pemberdayaan Santri di Pondok Pesantren Hasyim Asy’ari Jepara - Rizkiyani, Kaysa Adinda; Rohman, Fathur (Program Pascasarjana Universitas Islam Tribakti Lirboyo Kediri, 2025)
The phenomenon of gender inequality in pesantren education stands as a significant challenge, especially related to the low participation of female students, which results in inequality in learning opportunities. A solution is needed through a systematic approach to strengthen gender education equality to create a more just and inclusive environment for all students. This study describes the challenges and strengths of gender equality education at Hasyim Asy'ari Jepara Islamic Boarding School. This qualitative research uses the case study method. Data collection used interview techniques with caregivers, teachers, and students, observation of pesantren activities, and document analysis. The results showed that the reinforcement of gender equality education was carried out by implementing an inclusive curriculum and participatory learning methods, thus providing equal opportunities for male and female santri. Second, training for teachers and students should be organized. Third, providing opportunities for female santri participation. Fourth, continuous evaluation. The results of this study are expected to be an example for other pesantren who apply the principles of gender equality that are fair and inclusive to create a supportive educational environment for all students.